The effectiveness of small group discussion in writing report text - Sari, Ika Purnama; Siregar, Epi Supriyani; Roslaini, Roslaini; Muljo, Ariyani; Khairas, Eri Ester; Setiawan, Ari (Journal of English Language and Pedagogy, 2024)
Lack of interest in writing individually by students makes writing activity as one of the four language skills pay less attention to the students. Creating small Group Discussion is one method that can help students improve their learning achievement, especially in improving their writings. This research was intended to know the effectiveness of Small Group Discussion Technique on students’ achievement in writing report text at Madrasah Aliyah Negeri (MAN) Pematang Siantar. The populations of this research were 38 eleventh class students of Madrasah Aliyah Negeri (MAN) Pematang Siantar. The samples of this research were taken from 38 students (XI IPA 1).). The students’ achievement was measured l the students’ writing through pretest and posttest. The data were analyzed by using SPSS program. The pretest result shows the means score is 60.13 with the highest score is 70 and the lowest score is 50, while the post test result shows the means score is 60.13 with the highest score is 70 and the lowest score is 50. As the T-Test result, the significant value of Small Group Discussion  is 0.000 <0.05. The different scores between the Pre Test and the Post Test, and the T-test results show that there are differences between scores before and after Small Group Discussion technique were applied to the students. That means there is the effectiveness of Small Group Discussion on student’s achievement in writing Report Text